The Application of Sharia Economic Law Based on the Decision of the Palangka Raya Court Religious Number 217/PDT.G/2024/PA.PLK to the Legal Culture of Central Kalimantan - Almadani; Silma Nafiatur Rahmah; Sabarudin Ahmad (Faculty Sharia of State Islamic University (UIN) Palangka Raya, 2024)
Write down here your paper’s abstract in one paragraph, Sylfaen font size 12 with single spacing, no more than 250 words. The abstract is not an “introduction”, or the conclusion of the discussion. The abstract should be typed as concise as possible and should be composed of: problem statement, method, scientific finding results, and short conclusion. Other important matters discussed in the paper that significantly contribute to the final result of the research may be noted here, but you have to consider, however, the limited space of the abstract. The results of the research on the rejection of administratively incomplete lawsuits also underline the importance of sharia economic law literacy, both among the public and legal actors. This decision illustrates that the principles of sharia law, such as the prohibition of gharar and the application of maqashid sharia, especially hifz al-mal, can go hand in hand with the rules of positive law, thus creating justice and legal certainty for the litigants. This is in accordance with the legal culture of Huma Betang in accordance with sharia economic law such as the prohibition of gharar and the application of maqashid sharia, especially hifz al-mal, as well as Huma Betang which upholds equality and equality in making a decision, in order to uphold the philosophical values of the wisdom of the Dayak indigenous people of Central Kalimantan.